2020
DOI: 10.1177/0961203320947151
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of lupus nephritis in Saudi lupus patients: A retrospective observational study

Abstract: Objectives Systemic lupus erythematosus (SLE) is a chronic autoimmune multi-systemic disorder of the connective tissue, characterized mainly by involvement of the skin, joints, kidneys, and serosal membranes. It affects females particularly at childbearing age more commonly than males. Lupus nephritis affects around half of patients with SLE. Data about SLE and lupus nephritis in Saudi Arabia are still scarce. In this study, we aimed to evaluate the prevalence, clinical and laboratory findings of SLE and diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 18 publications
7
14
1
Order By: Relevance
“…Three separate Saudi Arabian studies showed that more patients were prescribed MMF (47%–75%) than CYC (18%–43%) as induction therapy. 40 – 42 The use of hydroxychloroquine was referenced in one of these studies, and was prescribed to all patients in the study population; this is consistent with current APLAR treatment recommendations. 13 , 40 Another study identified that 20% of patients who received induction therapy were prescribed a higher dose of CYC (NIH protocol) versus approximately 12% on a lower dose (Euro Lupus protocol).…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…Three separate Saudi Arabian studies showed that more patients were prescribed MMF (47%–75%) than CYC (18%–43%) as induction therapy. 40 – 42 The use of hydroxychloroquine was referenced in one of these studies, and was prescribed to all patients in the study population; this is consistent with current APLAR treatment recommendations. 13 , 40 Another study identified that 20% of patients who received induction therapy were prescribed a higher dose of CYC (NIH protocol) versus approximately 12% on a lower dose (Euro Lupus protocol).…”
Section: Resultsmentioning
confidence: 69%
“… 40 – 42 The use of hydroxychloroquine was referenced in one of these studies, and was prescribed to all patients in the study population; this is consistent with current APLAR treatment recommendations. 13 , 40 Another study identified that 20% of patients who received induction therapy were prescribed a higher dose of CYC (NIH protocol) versus approximately 12% on a lower dose (Euro Lupus protocol). 42 Separately, findings from a randomised clinical trial (RCT) in Saudi Arabia showed that the use of induction therapy of low-dose CYC (5 mg/kg) was as effective as a higher dose (10 mg/kg), resulting in similar rates of remission and fewer side effects in a Saudi Arabian patient population with Class IV LN.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…[ 1 ] Although the pathogenesis of SLE has not been fully understood, loss of self-tolerance and activation of autoreactive T and B cells occurs, leading to the production of pathogenic autoantibodies and tissue injury that characterize the disease. [ 2 ] Vasculitis is inflammation of blood vessel wall,[ 3 ] characterized by infiltration of inflammatory cells and subsequent necrosis of vessel walls. [ 4 ] The term secondary vasculitis is used to describe inflammation of blood vessels occurring as a complication of underlying disease process (mainly systemic autoimmune diseases as SLE) or triggered by exogenous factors such as infection, drugs, or malignancy.…”
Section: Introductionmentioning
confidence: 99%